Soldier and me. - Line, David (New York Harper & Row, 1965)
A large print edition of the adventures of an English schoolboy and a Hungarian immigrant he has befriended, as they witness a murder and flee desperately across the snowy English countryside.
Keywords: Adventure and adventurers -- Fiction; Large type books